West African Economic and Monetary Union : Staff Report on Common Policies of Member Countries-Regional Consultation on Economic Issues and Policies-Staff Report, Public Information Notice Informational Annex, Staff Statement, Executive Director's Statement. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
In 2010, average inflation has remained low in all West African Economic and Monetary Union (WAEMU) countries, but has edged up in the second half of the year. After a moderate fiscal easing by about 1 1\2 percentage points of GDP in 2009, mostly the result of higher capital spending, the area-wide average deficit is estimated to have declined slightly to 3.1 percent of GDP in 2010. A compression of imports in 2009, the region's external current account deficit is estimated to have returned to about 5 1\2 percent of GDP in 2010.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet